Aprendizagem baseada em problemas: saúde e educação numa tessitura interdisciplinar - Gentil, Rosana Maura (2009)
The investigation was a medical context, taking the Course of Medicine, University of São Paulo City - UNICID. Assumed objective of expanding the research horizon of understanding of Problem Based Learning (PBL). For that sought to analyze the theoretical frameworks that support the Education Program of course, present the main principles of the Problem-Based Learning and broaden the understanding of this methodology. To trace the path of research, I have relied on a qualitative approach was document and literature, consisting of reading and analyzing texts. This research built - if the borders between health and education, in a zone of intersection that is established, when you want to reflect on and interact with researchers in both areas. Among the authors consulted include: Fourez, Lenoir, Bruner, Barrows, Zabala, Dewey, Mamede, Vygotsky, Josso, Coll, Freire, Schmidt, Ausubel, and Larossa Bondia. Um greater knowledge of his ideas have helped me to identify four dimensions of problem situations potentiating the process of teaching and learning that guided the analysis of texts: interdisciplinary dimensions, relational, experiential and problem-solving. Based on the road trip we can say that the problem situations, and foster dialogue between disciplines, introduces us to a logic that connects to perceive and articulate the relationship between parties and between them and the whole. ABP seeks to articulate knowledge of various orders. This methodology as opposed to others that they are the centers of the territories disciplinary structure at the edges of these territories, as proposed problems require students to transit from various disciplines also favoring a cognitive, affective and political - social more differentiated.